M3814, a DNA-PK Inhibitor, Modulates ABCG2-Mediated Multidrug Resistance in Lung Cancer Cells - Wu, Zhuo-Xun; Peng, Zheng; Yang, Yuqi; Wang, Jing-Quan; Teng, Qiu-Xu; Lei, Zi-Ning; Fu, Yi-Ge; Patel, Ketankumar; Liu, Lili; Lin, Lizhu; Zou, Chang; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
M3814, also known as nedisertib, is a potent and selective DNA-PK inhibitor under phase 2 clinical trials. ABCG2 is a member of the ATP-binding cassette (ABC) transporter family that is closely related to multidrug resistance (MDR) in cancer treatment. In this study, we demonstrated that M3814 can modulate the function of ABCG2 and overcome ABCG2-mediated MDR. Mechanistic studies showed that M3814 can attenuate the efflux activity of ABCG2 transporter, leading to increased ABCG2 substrate drugs accumulation. Furthermore, M3814 can stimulate the ABCG2 ATPase activity in a concentration-dependent manner without affecting the ABCG2 protein expression or cell surface localization of ABCG2. Moreover, the molecular docking analysis indicated a high affinity between M3814 and ABCG2 transporter at the drug-binding cavity. Taken together, our work reveals M3814 as an ABCG2 modulator and provides a potential combination of co-administering M3814 with ABCG2 substrate-drugs to overcome MDR.